The prevalence and concentration of bacillus cereus in retail food products in Brisbane, Australia - Eglezos, S.; Huang, B.; Dykes, Gary; Fegan, N. (2010)
Illness associated with Bacillus cereus may be underreported as very few of those affected seek medical attention owing to the mild nature and short duration of symptoms. For this reason there is little information on the prevalence and concentration of this pathogen in retail food products. A total of 1263 retail food samples were examined for B. cereus using the Australian Standard 1766.2.6 (1991): spread plate technique on polymyxin pyruvate egg yolk mannitol bromothymol blue agar, of which the limit of detection was log 10 2.0cfu/g. Bacillus cereus was not detected in samples of skim milk powder, sandwiches, sushi, fresh beef mince, tortillas, or shelf stable stir-fry sauces. Bacillus cereus was detected in the following food samples: uncooked pizza bases (1 of 63 samples, log10 count of 2.0cfu/g), cooked pizzas (8 of 175, mean log10 3.4cfu/g), cooked meat pies (7 of 157, mean log10 2.2cfu/g), cooked sausage rolls (5 of 153, mean log10 2.6cfu/g), processed meats (1 of 350, log10 3.3cfu/g), and raw diced chicken (3 of 55, mean log10 4.3cfu/g). It appears that composite food products have more positive detection samples because the numerous ingredients may introduce spores into the foods. This study provides valuable data on the distribution, prevalence, and concentration of B. cereus in selected retail products. © 2010, Mary Ann Liebert, Inc.